Influences of the Literary Canon: Statistical Analysis of High School Reading Lists in the Czech Republic: en - Hrdličková, Marcela; Křápek, Milan (Bohemistyka, 2024)
This study focuses on the analysis of the school lists of literary works for the graduation exam, which were published for the exam in the school year 2019/2020. The aim of this pilot study is to determine if there is a relation between school lists and the state-certified list, which is also a determining factor for the graduation exam in the Czech language and literaure. Questions regarding the influence of the school list on the success rate of the graduation exam or the relation between the type of school and the size of the list and the graduation exam are also discussed. We analyze the lists from 72 schools from the South Moravian Region in the Czech Republic. In total, we are dealing with 7 551 items, on which the correlation analysis, regression analysis and cluster analysis are applied.